Enhancement of electrochemical properties of niobium‐doped LiFePO4/C synthesized by sol–gel method. Issue 8 (15th April 2018) - Jiang, Ao; Wang, Xinlu; Gao, Musen; Wang, Jinxian; Liu, Guixia; Yu, Wensheng; Zhang, Hongbo; Dong, Xiangting
Abstract : LiFePO4 /C and LiFe1– x Nb x PO4 /C composites were synthesized using a sol–gel method. The influence of niobium doping on the constitution, morphology, and electrochemical properties of the samples was studied in detail. X‐Ray diffraction patterns indicate that appropriate Nb doping does not alter seriously the structure of LiFePO4 . Electrochemical characterization of the electrodes showed that the Li‐ion batteries based on LiFe1– x Nb x PO4 /C electrode exhibited better charge/discharge performance than those based on LiFePO4 /C. The LiFe0.95 Nb0.05 PO4 /C‐based cell had the specific capacity of 157, 121, and 85 mAh/g at 0.2, 2, and 5 C, respectively, in comparison with 126, 94, and 52 mAh/g for the LiFePO4 /C cell. The results show that the addition of niobium promotes the electrochemical performance of the materials especially at high charge/discharge rates of the battery. Abstract : Niobium‐doped LiFePO4 /C, which were prepared by the sol–gel method for the first time, exhibited good discharge performance and cycle stability at high rates (2 and 5 C) when used as the cathode material for Li‐ion batteries.